Conversation with Thomas Pavel (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2011)
Below are the videos of the interview recorded in Paris in May 2011.Conversation with Thomas Pavel.Part 1 of 3 Part 2 of 3 Part 3 of 3